Survival strategies of host, parasite, and vector in human Malaria - Mandal, Fatik Baran (Researcher Bulletin of Medical Sciences, 2023)
Malaria, the best example of infectious protozoan diseases, has been tremendously impacted the human genome. The global spread of malaria reflects the successful adaptations of Plasmodium in human host and its Anopheles vector. The potential defences of Plasmodium deal with diverse mechanisms of host immunity and persist in human with headstrong success. In an evolutionary arms race, human has developed malaria protective polymorphisms to survive. These polymorphisms provide safeguards human against the malaria. Anopheles has developed pesticide resistance for their survival. This article briefs the interactions among Plasmodium, Anopheles, and human to provide evolutionary insight on malaria related genetic polymorphisms and to determine the evolutionary fitness of human, Plasmodium and Anopheles.